Assessment of Distance Learning in the Algerian Universities during the COVID-19 - Boutkhil Guemide (International Islamic University Islamabad, 2021)
Like many countries in the world, Algeria has been hit by the Corona virus, and as a result, the Algerian government has taken serious measures to deal with the current situation. In this context, the Algerian ministry of higher education and scientific research has instructed universities to perform online teaching and learning through regular, established eLearning platforms, as a step towards reducing the spread of the Corona virus. The present paper provides an assessment of the online learning electronic system provided by the Algerian universities during the pandemic. Basically, the research relies on students’ and teachers’ questionnaires as the undertaking tool to gather valid data in order to analyze and highlight the shortcomings of the online learning. The research results indicated that total reliance on online learning was according to strategies and planned learning objectives as it needs a solid platform for its total implementation. The research concluded with some recommendations which should be taken into account for better implementation of online learning electronic system in the Algerian higher education context.